Selection of rhythm intervention strategies in atrial fibrillation patients with cancer and efficacy and safety of catheter ablation - Wang, Xin; Han, Xu; Yang, Xiaolei; Hidru, Tesfaldet Habtemariam; Wang, Chengfang; Xia, Yunlong; Che, Ying (Frontiers in Cardiovascular Medicine, 2024)
BackgroundThe risk of comorbidity of cancer is increased in atrial fibrillation (AF) patients, which is a massive challenge for clinical management in cardiovascular settings. This study aimed to analyze whether cancer affects the decision of radiofrequency ablation and to explore the efficacy and safety of radiofrequency ablation in AF patients with cancer.MethodsWe conducted a retrospective cohort study of patients who were first diagnosed AF and identified who were with cancer. The propensity score matching method was utilized to balance the differences between the cancer and non-cancer groups. Logistic regression analysis was used to study the related factors affecting the ablation of AF. Cox regression analysis was used to evaluate the effect of cancer on the recurrence of AF after radiofrequency ablation.ResultsAmong 9,159 patients who were first diagnosed AF, the prevalence of cancer was 4.48%. Cancer did not affect the decision of rhythm intervention in AF patients (P = 0.46). There was no significant difference in the incidence of perioperative complications, bleeding events, and embolization events between cancer and non-cancer groups (P = 1.000). The median follow-up time was 342 (293,866) days, and 45 patients had AF recurrence. Multivariable Cox regression showed no statistically significant relationship between concomitant cancer and AF recurrence after radiofrequency ablation (hazard ratio = 0.82, 95% confidence interval 0.36–1.83, P = 0.62).ConclusionsThe combination of cancer did not affect the decision of patients to perform ablation therapy. Radiofrequency catheter ablation could be used as a strategy to maintain long-term sinus rhythm in patients with concomitant cancer without affecting AF recurrence.